Проектировочный расчет передач типа А - Филипенков, А. Л. (НТУ "ХПИ", 2006)
Представлено метод проектувального розрахункуi раціональної розбивки передатного відношення мiж ступiнями планетарних передач з урахуванням критерiïв контактноїi изгибноï мiцностi зубчастих колiсi довговiчностi опор сателiтiв.

A method of designing calculation and rational selection of transmission ratio between steps of planetary gears, taking into account the contact and bending resistance criteria of cog-wheels and durability of satellite supports is submitted.
Keywords: планетарная передача; сателлиты; зубчатое колесо; подшипники качения; кинематический параметр